Spain, Reincarnated: Julio Medem’s Caótica Ana and New Spanish Media(tion) in the World - Susan Martin-Márquez (Studies in 20th & 21st Century Literature, 2009)
Spanish director Julio Medem’s visually stunning yet controversial 2007 film Chaotic Ana was panned for its ostensibly Manichaean treatment of gender relations and its crudely scatological ending, both of which have distracted attention from the work’s fascinating incursions into global politics. While the film’s complex layering of hawk and dove imagery figures centuries of male violence against women, it is also imbricated with an extended meditation on the divergent roles of the United States and Spain on the contemporary world stage. Through the male protagonist Said, a Saharawi painter, the film artfully shifts postcolonial guilt for the fate of the Western Sahara from the former colonizer Spain to the United States. Even as the film obfuscates Spain’s multifaceted imperial past, it engages in a withering indictment of U.S. foreign policy in the post-9/11 era, indicating through a web of symbolic references to the Statue of Liberty that Americans have turned away from their once-vaunted mission. That mission, the film (problematically) suggests, must now be taken up by Spain, which, together with other enlightened European nations, serves as a beacon for global justice, drawing upon the Spanish National Court’s declaration of universal jurisdiction to prosecute the U.S. government’s neocolonial crimes against humanity.
Keywords: Julio Medem; Caótica Ana; Chaotic Ana; Spanish film; Spain; gender; Manichaean; United States; men; women; imperialism; foreign policy